Britain since 1688 - Barczewski, Stephanie L., author.
1 online resource
Keywords: "Now in its second edition, Britain since 1688 is an accessible and comprehensive introduction to British History from 1688 to the present day that assumes no prior knowledge of the subject. Chronological in structure yet thematic in approach, the book guides the reader through major events in British history from the Glorious Revolution of 1688, offering extensive coverage of the British Empire and continuing through to recent events such as Britain's exit from the European Union. Fully revised and updated using the most recent historical scholarship, this edition includes discussion of the Brexit referendum and Britain's subsequent exit from the European Union, along with increased coverage of Britain's imperial past and its legacy in the present. New sidebars on themes such as race, immigration, religion, sexuality, the presence of empire and the experience of warfare are carried across chapters to offer students current and relevant interpretations of British history. Written by a team of expert North American university professors and supported by textboxes, timelines, bibliographies, glossaries and a fully integrated companion website, this textbook provides students with a strong grounding in the rich tapestry of events, characters, and themes that encompass the history of Britain since 1688"--